Psycho-Spiritual Consciousness and Its Relevance to Muslim Minority Communities: Integrating William James and Al-Ghazali - Arroisi, Jarman; Anam, Hafidz Muhammad; Amrullah, Khasib; Nasuha, Moh Yordan (Institut Agama Islam Negeri (IAIN) Manado, 2025)
This study examines the concept of consciousness in the thought of William James and Abu Hamid al-Ghazali through an ontological, epistemological, and teleological comparison, and explores its relevance to the psycho-spiritual experience of Muslim minority communities. Employing a qualitative philosophical-comparative method based on library research of primary and secondary texts, the study proceeds through four analytical stages: hermeneutical reading, conceptual mapping, comparative analysis, and integrative synthesis. The findings reveal that James conceives consciousness as a continuous, selective, and adaptive stream of subjective experience grounded in empirical-pragmatic epistemology, while al-Ghazali conceives it as a spiritually illuminated state of the soul (nafs) attained through tazkiyat al-nafs, muraqabah, and muhasabah, oriented toward ma'rifatullah. Despite their divergent metaphysical foundations, both thinkers affirm the transformative, ethical, and meaning-making dimensions of inner experience. This study formulates a three-axis psycho-spiritual integrative model, namely the cognitive-adaptive, spiritual-purification, and ethical-social axes, which demonstrates that James's adaptive consciousness and al-Ghazali's spiritual disciplines function as complementary resources for Muslim minority communities navigating identity negotiation, spiritual resilience, and social participation in non-Muslim majority pluralistic contexts. The model contributes to Islamic psychology and minority religious studies while offering a conceptual foundation for consciousness-based approaches to Islamic education and community empowerment.